2020
DOI: 10.3389/fnmol.2020.00080
|View full text |Cite
|
Sign up to set email alerts
|

Integrated Metabolomics and Proteomics Analysis Reveals Plasma Lipid Metabolic Disturbance in Patients With Parkinson’s Disease

Abstract: Parkinson's disease (PD) is a common neurodegenerative disease in the elderly with a pathogenesis that remains unclear. We aimed to explore its pathogenesis through plasma integrated metabolomics and proteomics analysis. The clinical data of consecutively recruited PD patients and healthy controls were assessed. Fasting plasma samples were obtained and analyzed using metabolomics and proteomics methods. After that, differentially expressed metabolites and proteins were identified for further bioinformatics ana… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(45 citation statements)
references
References 43 publications
4
41
0
Order By: Relevance
“…This unbiased and data-driven study provided a foundational resource for the PD community through a publicly available pathways browser. Pathways previously implicated by genetics and functional studies also found to be significant in this study include endocytic trafficking [ 61 , 62 ], autophagic-lysosomal function [ 51 , 63 ], mitochondrial function [ 64 , 65 ], protein aggregation [ 66 ], neuronal transmission [ 67 ], lipid metabolism [ 68 , 69 ], and certain inflammatory pathways [ 70 , 71 ] ( Figure 1 ). It has also been shown that similar pathways can be deficient in both familial and common forms of PD [ 51 , 62 ] and multiple networks can overlap or a single pathway can act alone.…”
Section: Genetics As a Tool To Nominate Network To Be Targeted Inmentioning
confidence: 73%
“…This unbiased and data-driven study provided a foundational resource for the PD community through a publicly available pathways browser. Pathways previously implicated by genetics and functional studies also found to be significant in this study include endocytic trafficking [ 61 , 62 ], autophagic-lysosomal function [ 51 , 63 ], mitochondrial function [ 64 , 65 ], protein aggregation [ 66 ], neuronal transmission [ 67 ], lipid metabolism [ 68 , 69 ], and certain inflammatory pathways [ 70 , 71 ] ( Figure 1 ). It has also been shown that similar pathways can be deficient in both familial and common forms of PD [ 51 , 62 ] and multiple networks can overlap or a single pathway can act alone.…”
Section: Genetics As a Tool To Nominate Network To Be Targeted Inmentioning
confidence: 73%
“…At our knowledge, this is the first report describing a specific metabolic fingerprint of MSK and the possible involvement of sphingomyelin in the MSK-associated biological impairment. Instead, alterations in the metabolism of sphingomyelin and other sphingolipids have been extensively reported in other diseases including neurodegenerative [Alzheimer's disease ( 31 ), Parkinson's ( 32 ), multiple sclerosis ( 33 ), Lewy body dementia ( 34 )], vascular ( 35 ), and bone disorders ( 30 ).…”
Section: Discussionmentioning
confidence: 99%
“…Serotonin reuptake inhibitors and serotonin norepinephrine reuptake inhibitors are usually used as part of the preferred initial treatment (Katzman et al, 2014 ) with response rates in the range of 30–50% (Reinhold and Rickels, 2015 ). We have performed a number of studies about this issue before (Dong et al, 2017a , b ; Dong et al, 2018a ; Chen et al, 2020 ; Hu et al, 2020 ). The main aim of this study was to assess whether dopaminergic dysregulation can be detected in anxiety and obsessive disorder with any degree of consistency and specificity.…”
Section: Discussionmentioning
confidence: 99%